THE PROPERTIES OF ROUGH V-COEXACT SEQUENCE IN ROUGH GROUP - Hafifullah, Desfan; Fitriani, Fitriani; Faisol, Ahmad (PATTIMURA UNIVERSITY, 2022)
In ring and module theory, the concept of an exact sequence is commonly employed. The exact sequence is generalized into the U-exact sequence and the V-coexact sequence. Rough set theory has also been applied to a variety of algebraic structures, including groups, rings, modules, and others. In this study, we investigated characteristics of a rough V-coexact sequence in rough groups